Strawberry Consumption Associated with Reduced Alzheimer's Dementia Risk (FS05-06-19) - Agarwal, Puja (Curr Dev Nutr, 2019)
OBJECTIVES: Strawberries have been identified to have antioxidant and anti-inflammatory properties that improve neuronal function and cognition, mostly in animal studies. It is not known whether consumption of strawberries is associated with risk of Alzheimer's dementia (AD). The objective of this study is to investigate the relation between strawberry intake and Incident Alzheimer's dementia. METHODS: The study was conducted in 925 participants (mean age: 81.2 ± 7.2 years, mean education: 15 ± 3 years) of the Rush Memory and Aging Project who completed a food frequency questionnaire and had at least two annual neurological evaluations. Frequency of strawberry consumption was modeled as a continuous variable with values of 0 for never or less than once a month; 0.5 for 1–3 times/month; 1.0 for once -per week, and 2 for 2–4 times/week. The diagnosis of AD was based on criteria of the joint working group of the National Institute of Neurological and Communicative Disorders and Stroke and the AD and Related Disorders Association. Data was analyzed using proportional hazard models adjusted for age, sex, education, physical activity, participation in cognitive activities, dietary intake of other fruits, and total calorie intake. RESULTS: A total of 235 participants developed Alzheimer's dementia over the mean follow-up of 6.5 (±3.6) years. Higher strawberry intake was associated with reduced risk of Alzheimer's dementia (HR = 0.76, 95% CI: 0.60–0.96). Participants who consumed strawberries more than once/week were 32% less likely to develop AD (HR = 0.68, 95% CI: 0.48–0.97) compared with non-consumers. These associations remained after further adjustment for green leafy vegetable intake and APOE- ɛ4 status. CONCLUSIONS: Higher strawberry consumption may reduce the risk of Alzheimer's dementia. FUNDING SOURCES: California Strawberry Commission.